Geology of the Kokchetav UHP‐HP metamorphic belt, Northern Kazakhstan - Y. Kaneko; S. Maruyama; M. Terabayashi; H. Yamamoto; M. Ishikawa; R. Anma; C. D. Parkinson; T. Ota; Y. Nakajima; I. Katayama; J. Yamamoto; K. Yamauchi (Island Arc, 2000)
Ultrahigh‐pressure metamorphic (UHPM) rocks of the Kokchetav Massif of Kazakhstan contain metamorphic microdiamond and coesite inclusions inside rigid capsules such as garnet and zircon. Precambrian protoliths of the UHPM rocks were metamorphosed at around 530 Ma, at pressures of about 7 GPa, which suggests that crustal protoliths were subducted to depths of over 200 km. Primary UHPM minerals are poorly preserved due to partial obliteration by subsequent Barrovian overprint during exhumation and later collision events in Caledonian times. We report the results of detailed mapping of the Kokchetav Massif and use structural data to propose intrusion and exhumation mechanisms for the UHPM rocks. Detailed mapping revealed that many subvertical structures in the ultrahigh‐pressure–high‐pressure (UHP–HP) units were formed due to later folding. The primary structure appears to be subhorizontal and the total thickness of the UHP rocks is estimated at around 2 km. The first order structure is sandwich‐like; that is, the UHP–HP units are separated from underlying low‐P metamorphic rocks of the Daulet Series and from feebly metamorphosed to unmetamorphosed sedimentary strata on the top by subhorizontal faults. Kinematic indicators show top‐to‐the‐south sense of shear along the top, and top‐to‐the‐north displacement along the bottom boundaries. These shear senses, together with the observed metamorphic gradients, suggest that the thin UHPM sheet was extruded toward the north. We consider wedge extrusion to have been the most effective mechanism for the exhumation of the UHPM rocks.